Unsayable Music : Six Reflections on Musical Semiotics, Electroacoustic and Digital Music - Chagas, Paulo C. (Book collections on Project MUSE., 2014)
Profound theoretical and philosophical approach to contemporary music.Unsayable Music presents theoretical, critical and analytical reflections on key topics of contemporary music including acoustic, electroacoustic and digital music, and audiovisual and multimedia composition. Six essays by Paulo C. Chagas approaching music from different perspectives such as philosophy, sociology, cybernetics, musical semiotics, media, and critical studies. Chagas's practical experience, both as a composer of contemporary music and sound director of the Electronic Music Studio of Cologne, nourishes his obser.